Eventos perigosos em unidades de filtração de etas do Brasil: estudos de caso - Dantas, Angela Di Bernardo; Bernardo, Luiz Di; Polizel, Lucas; Liani, Jennifer; Conceição, Natalia Ribeiro da; Killer, Natalia Aparecida (International Workshop for Innovation in Safe Drinking Water, 2022)
The presence of pathogenic protozoa in surface water sources is widely known and reported in literature. In conventional water treatment plants (WTPs), as most of the Brazilian WTPs, filters are considered the main barrier to such microorganisms. As part of the elaboration of Water Safety Plans (WSP), diagnostics were carried out in the filtration units of six different WTPs in Brazil, with the identification of hazardous events that may contribute to the presence of hazard (protozoa and other pathogenic microorganisms) in the treated water. All WTPs had at least one hazardous event related to filtration units. Such events are mainly of hydraulic or infrastructural nature; or, in some cases, operational. Control measures were indicated to control associated risks, which are usually high, since the effectiveness of disinfection is reduced when filters do not perform properly. Operational measures were able to increase water safety in very short term, whilst infrastructural measures may demand a longer period to be implemented.